Development of a Web-Based Performance Index Assessment System for Hazardous and Toxic Waste Management - Jenni Ria Rajagukguk; Helen Octory (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to develop a web-based performance index assessment system for hazardous and toxic waste management by integrating technical and supporting indicators using the Multi-Criteria Decision Making (MCDM) and Analytic Hierarchy Process (AHP) approaches. The study also examines the system’s role in supporting transparent environmental evaluation and applied environmental learning. Methods: A quantitative research and development approach was employed using the MCDM-AHP method. Data were collected through literature review, regulatory analysis, expert judgment involving five environmental experts, and system simulations on three industrial entities with different waste management characteristics. The system was developed using a Python-Django framework and PostgreSQL database. Findings: The results indicate that the developed system provides objective, transparent, and consistent environmental performance assessments, with performance index values ranging from 60% to 92%. Industrial entities with higher levels of digitalization and standardized environmental management systems achieved better performance scores. The integration of environmental impact assessment also improved risk identification and monitoring effectiveness. Research Implications: The findings imply that digital-based environmental assessment systems can strengthen accountability, operational efficiency, and data-driven decision-making in hazardous waste management. However, the study is limited by the small number of expert respondents and simulation entities, which may affect broader generalizability. Originality: This study offers a novel contribution by integrating environmental performance indicators, MCDM-AHP analysis, and a web-based digital assessment platform into a unified hazardous waste management evaluation system that can also support applied environmental education and sustainability-oriented industrial governance.